Utilization of Main Library Information Resources amidst Pandemic - Yap, Benilda; Martinez, Irene; Rian, Clowie (JPAIR Institutional Research, 2022)
Libraries are depositories of print and non-print information resources, vital in any institution for preserving and conserving human knowledge. As a result of the pandemic, many libraries were forced to close, significantly impacting how people utilized libraries. The primary purpose of the study is to determine the level of utilization of BC Main Library Information Resources by fourth-year undergraduate students amidst the COVID-19 pandemic. Furthermore, the study attempted to identify the information resources available at BC Main Library, identify the problems impeding optimal utilization of library information resources during the pandemic, and offer solutions to the challenges discovered. This employed a descriptive quantitative survey method, with respondents receiving questionnaires online. Findings revealed that the majority of respondents acknowledged the availability of information resources in the Bicol College Main Library, and they utilized these resources even amidst the pandemic. Due to the limits imposed by the pandemic, students had challenges using these resources. The suggested measures are critical in addressing students’ difficulties when using these resources. More studies on improving awareness should be performed, and the provision of orientations, training, and capitalizing on new technology was highlighted as measures to promote library awareness and utilization.